Analisis Pengaruh Harga dan Kualitas Produk terhadap Loyalitas Konsumen di Cafe Meuligo Agam, Meulaboh - Wariah, Ayu; Chairiyaton (Medan Resource Center, 2025)
This study examines the influence of price and product quality on consumer loyalty at Café Meuligo Agam, a well-known culinary business located in Meulaboh, West Aceh Regency. The research was motivated by variations in consumer perceptions regarding taste preferences and concerns related to relatively high product prices, particularly among middle- and lower-income consumers. The study addresses the question of whether price and product quality significantly affect consumer loyalty both partially and simultaneously. A quantitative approach was employed using primary data collected from 100 respondents. Data were analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The findings demonstrate that price and product quality exert significant partial and simultaneous effects on consumer loyalty. Product quality contributes positively to customer retention through consistent service and consumer satisfaction, while pricing strategies influence purchasing decisions and long-term loyalty. The study concludes that maintaining competitive pricing and consistent product quality constitutes a crucial strategy for strengthening consumer loyalty in the culinary business sector.